Data center traffic scheduling strategy based on Fibonacci tree optimization algorithm - Yaomin WANG; Xia WANG; Yi DONG; Songhai ZHANG; Xinling SHI (Tongxin xuebao)
To improve traffic scheduling capabilities in network provider data centers,both network structure and network traffic flow were considered at the same time.The analysis prediction and online scheduling mechanism was proposed in data center based on software defined networking (SDN).Aiming at the multi-dimensional,multi-constrained and multi-modal problems of traffic flow scheduling in data centers,the traffic flow scheduling strategy based on Fibonacci tree optimization (FTO) algorithm was proposed.FTO algorithm was embedded into two stages of analysis prediction and online scheduling,took it advantage of global local alternating and multi-model optimization characteristics,the optimal solution and suboptimal solutions of traffic scheduling had been got at one time.The emulator result shows that,the FTO traffic scheduling strategy can schedule traffic in data centers reasonably,which improves the load balancing capability of network providers' data centers effectively.